The Impacts of State-specific LGBTQ Policies on Career Planning Among Medical Students in the United States - Katrina Hayes (International Journal of Medical Students, 2025)
BACKGROUND: According to the American Civil Liberties Union, a record 510 anti-LGBTQ bills were filed across the United States in 2023.1 These bills impact a wide range of LGBTQ rights. Amid these trends in legislation, many LGBTQ medical students face amplified stressors when deciding where to train and eventually practice. This study aims to understand how state-specific LGBTQ legislation and students’ perceptions of safety shape their decision-making while pursuing careers in medicine. METHODS: Between March and April of 2024, medical students across the United States who self-identify as LGBTQ were surveyed via university-affiliated LGBTQ student organizations. The survey assessed students’ perceived level of safety and comfort with LGBTQ status among different social networks. Students also rated their knowledge of anti-LGBTQ legislation and classified the degree to which this legislation impacts their choice of residency program. RESULTS: Survey data was collected from 96 medical students from 14 different states. Participants reported feeling least comfortable/safe with hospital staff and most comfortable/safe with friends. Respondents reported that states’ LGBTQ legislation had a greater influence on their residency program applications in comparison to their prior medical school applications (p<0.001, CI [-1.15 to -0.68]). LGBTQ-identifying medical students perceived California and New York as safer compared to Florida and Texas (χ² = 330.57, df = 4, p<0.001). CONCLUSION: Amidst the multitude of factors influencing medical students’ decisions regarding residency programs, the level of LGBTQ acceptance within states emerges as a crucial consideration. With looming physician shortages, creating inclusive training environments is vital, given the profound influence of LGBTQ climates on career choices.